Constraining new physics from the first observation of coherent elastic neutrino-nucleus scattering - Papoulias, D. K.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2019)
The process of neutral-current coherent elastic neutrino-nucleus scattering, consistent with the Standard Model (SM) expectation, has been recently measured by the COHERENT experiment at the Spallation Neutron Source. On the basis of the observed signal and our nuclear calculations for the relevant Cs and I isotopes, the extracted constraints on both conventional and exotic neutrino physics are updated. The present study concentrates on various SM extensions involving vector and tensor nonstandard interactions as well as neutrino electromagnetic properties, with an emphasis on the neutrino magnetic moment and the neutrino charge radius. Furthermore, models addressing a light sterile neutrino state are examined, and the corresponding regions excluded by the COHERENT experiment are presented.